Reconstructing Maintenance Rights for Children Born of Rape: Beyond Nasab Doctrine toward State Responsibility - Budi Tresnayadi; Jajang Jamaluddin; Yayan Muhammad Royani; Khairani Dewi (Institut Agama Islam Negeri Curup, 2026)
Children born of rape face persistent uncertainty regarding long-term maintenance because Indonesian law separates child protection, criminal restitution, and family-based maintenance. While positive law emphasizes restitution and compensation, Islamic family law traditionally associates paternal maintenance with legally recognized nasab, creating a protection gap when paternal lineage cannot be established or enforced. This study examines the limitations of the nasab-based maintenance doctrine and formulates a maqāṣid-based model of responsibility for children born of rape. It employs doctrinal legal research using statutory, conceptual, comparative, and maqashid al-shari‘ah approaches. Legal materials include Indonesian legislation, court decisions, classical Islamic jurisprudence, and scholarly studies on children’s rights, lineage, and victim protection. The findings demonstrate that existing restitution mechanisms do not ensure continuous maintenance, while the dependence of maintenance on nasab may leave affected children without an effective responsible party. A purposive interpretation of hifz al-nafs, hifz al-nasl, and hifz al-mal supports treating maintenance as an independent child-protection entitlement rather than merely a consequence of legal lineage. This study proposes a layered responsibility model in which the perpetrator or proven biological father bears primary liability, while the state serves as a subsidiary guarantor when private responsibility cannot be identified or enforced. The model requires a state-managed child maintenance guarantee, periodic judicial assessment, and a right of recourse against the perpetrator. This reconstruction aligns Islamic legal reasoning with the best interests of the child and provides a sustainable framework for protecting children born of rape.